Molecular Nickel Thiolate Complexes for Electrochemical Reduction of CO2 to C1–3 Hydrocarbons - Du, Jiehao; Cheng, Banggui; Yuan, Huiqing; Tao, Yuan; Chen, Ya; Ming, Mei; Han, Zhiji; Eisenberg, Richard (Angewandte Chemie International Edition, 2023)
We report the unprecedented electrocatalytic activity of a series of molecular nickel thiolate complexes (1–5) in reducing CO2 to C1–3 hydrocarbons on carbon paper in pH‐neutral aqueous solutions. Ni(mpo)2 (3, mpo=2‐mercaptopyridyl‐N‐oxide), Ni(pyS)3− (4, pyS=2‐mercaptopyridine), and Ni(mp)2− (5, mp=2‐mercaptophenolate) were found to generate C3 products from CO2 for the first time in molecular complex. Compound 5 exhibits Faradaic efficiencies (FEs) of 10.6 %, 7.2 %, 8.2 % for C1, C2, C3 hydrocarbons respectively at −1.0 V versus the reversible hydrogen electrode. Addition of CO to the system significantly promotes the FEC1–C3 to 41.1 %, suggesting that a key Ni−CO intermediate is associated with catalysis. A variety of spectroscopies have been performed to show that the structures of nickel complexes remain intact during CO2 reduction. A series of bioinspired molecular nickel thiolate complexes exhibit impressive electrocatalytic activity for CO2 reduction on carbon paper, with a Faradaic efficiency of 41 % for hydrocarbons. C3 hydrocarbons were reported for the first time from molecular complexes.